USP45-mediated deubiquitination of HIV-1 Tat regulates viral transcription and latency - Miyakawa, Kei; Okura, Hiyori; Hatayama, Yasuyoshi; Nishi, Mayuko; Kimura, Hirokazu; Yamamoto, Hiroyuki; Hasegawa, Hideki; Matano, Tetsuro; Ryo, Akihide (Frontiers in Microbiology, 2026)
The HIV-1 Tat protein is regulated by post-translational modifications, particularly ubiquitination, but the full spectrum of deubiquitinating enzymes (DUBs) controlling HIV-1 transcription remains incompletely understood. We developed a NanoBRET-based screening system using a library of 120 DUB expression vectors and identified USP45 as a novel Tat-interacting DUB. Functional characterization revealed that USP45 specifically deubiquitinates Tat at lysine 19, targeting both K48-linked and K63-linked ubiquitin chains. Notably, USP45 overexpression suppressed Tat-dependent transcriptional activation and HIV-1 viral particle production, while USP45 knockdown enhanced both processes. Transcriptional profiling in latently infected J-Lat 8.4 cells using digital PCR revealed that USP45 primarily inhibits the initial stages of viral transcription, thereby contributing to the maintenance of the latent state by restricting downstream transcriptional processes. Furthermore, USP45 expression is induced by interferons, identifying it as an interferon-stimulated gene. These findings establish that USP45 functions as a host restriction factor that negatively regulates HIV-1 transcription by promoting Tat deubiquitination at lysine 19, representing a promising therapeutic target for controlling HIV-1 latency.